2020
DOI: 10.1016/j.mcp.2020.101580
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a rapid detection assay for severe fever with thrombocytopenia syndrome virus based on reverse-transcription recombinase polymerase amplification

Abstract: Development and evaluation of a rapid detection assay for severe fever with thrombocytopenia syndrome virus based on reverse-transcription recombinase polymerase amplification, Molecular and Cellular Probes (2020), doi: https://doi.Table of Abbreviations: dT-FAM Thymidine nucleotide carrying FAM fluorophore dT-BHQ1 Thymidine nucleotide carrying BHQ-1 quencher HHV Human herpesvirus LAMP loop-mediated isothermal amplification LOD Limit of detection PIV Parainfluenza virus RPA Recombinase polymerase amplification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…At present, the most focused molecular detection methods, such as polymerase chain reaction (PCR) and quantitative real-time polymerase chain reaction (qPCR), are not suitable for on-site detection of SFTSV, due to the requirements of sophisticated instruments and skilled personnel ( Sun et al, 2012 ). A series of isothermal amplification techniques have also been established to detect SFTSV, including loop-mediated isothermal amplification (LAMP) and recombinase polymerase amplification (RPA; Zhou et al, 2020 ; Sano et al, 2021 ). But these amplification technologies still show limitations in sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the most focused molecular detection methods, such as polymerase chain reaction (PCR) and quantitative real-time polymerase chain reaction (qPCR), are not suitable for on-site detection of SFTSV, due to the requirements of sophisticated instruments and skilled personnel ( Sun et al, 2012 ). A series of isothermal amplification techniques have also been established to detect SFTSV, including loop-mediated isothermal amplification (LAMP) and recombinase polymerase amplification (RPA; Zhou et al, 2020 ; Sano et al, 2021 ). But these amplification technologies still show limitations in sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%
“…After reading the full text of the articles, 103 were discarded, including 48 that did not use clinical patient samples or lacked data, 35 that were not on nucleic acid‐related diagnostic techniques, 14 that lacked reference standards, and 6 that were not on or related to SFTS. A final total of 16 articles were included, seven on RT‐PCR 19 , 20 , 24 , 25 , 26 , 27 , 28 and seven on RT‐LAMP, 16 , 21 , 29 , 30 , 31 , 32 , 33 and two that were on both RT‐PCR and RT‐LAMP. 15 , 34 A flowchart of the research process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Detection of SFTSV genome could be achieved by different nucleic acid detection techniques such as RT-PCR (13,(40)(41)(42)(43), real-time RT-PCR (23,28,41,(44)(45)(46)(47)(48), LAMP (24,(49)(50), as well as RPA (25,(51)(52).…”
Section: Nucleic Acid Detectionmentioning
confidence: 99%
“…After combining with the fluorescent detection reagent (FDR) method, results could be determined by observing a color change within 30 min (64). Jang et al developed a multiplex RT-LAMP to identify larger segments and GroES genes for SFTSV and Orientia tsutsugamushi (OT) (24). The sensitivity of the multiplex SFTSV/OT/Internal control (IC) RT-LAMP assay proved comparable to that of the commercial PowerChek™ SFTSV Real-time PCR (91.3% vs. 95.6%).…”
Section: Rapid Nucleic Acid Detectionmentioning
confidence: 99%
See 1 more Smart Citation